Energy Consumption Model Based on User Behavior to Support Solar Panel Selection: Case Study of Dental Clinic - Firdaus, Rifki; Suryadi, Kadarsah (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. Electricity consumption continues to rise alongside population growth and infrastructure development. Unfortunately, the majority of energy consumption is still reliant on fossil fuels. Commercial buildings and residences are major contributors to electricity consumption, accounting for 63.04% of the total usage. In the healthcare sector, clinics and hospitals also require significant electrical energy, contributing to a 21% rise in national electricity demand. Additionally, occupants' behavior influences electricity consumption by 30%. Faced with these challenges, the use of renewable energy, such as solar power, holds great potential for providing sustainable energy. This research aims to simulate energy consumption to aid in the selection of solar panel technology, considering occupant behavior. By understanding accurate electricity consumption, solar panels that meet the needs can be chosen to ensure long-term sustainability. Simulation of electricity consumption using dynamic system methods is performed to acquire daily electricity consumption data, a critical criterion in solar panel selection. The study's results indicate that user behavior in utilizing electrical appliances significantly impacts overall energy consumption. The study implies the importance of understanding behavior to properly recognize actual electricity consumption. Keywords: Energy consumption, simulation, system dynamic, user behaviour.